E-034 Endovascular internal trapping for ruptured dissecting vertebral artery aneurysms. (16th November 2010) - Yamamoto, D; Uemura, A; Fujii, M; Matsukawa, H; Kobayashi, N; Numaguchi, Y; Murakata, A; Shinoda, M; Ishikawa, R
Abstract : Purpose: Ruptured dissecting vertebral artery aneurysms should be treated immediately because of the high risk of rebleeding. The purpose of this retrospective study is to evaluate the efficacy of endovascular internal trapping by platinum coils for ruptured dissecting vertebral artery aneurysms. Materials and methods: We retrospectively reviewed 13 cases (eight men and five women; aged 50–80 years; mean 65 years) of acutely ruptured aneurysms of the vertebral artery treated by endovascular internal trapping between April 2003 and February 2010. Endovascular trapping was done by coil embolization of the dissected arterial segment, including the aneurysm. Evaluated subjects included success of the therapy, presence of rebleeding, procedural complication and other technical issues. Results: In all cases, endovascular internal trapping was done successfully. There was no case of rebleeding. Three cases in which perforating arteries to brainstem originated from the dissected segment had postprocedural medullary infarction. However, the neurological symptoms diminished during the follow-up period. Conclusion: Endovascular internal trapping is an effective and feasible therapy for ruptured dissecting aneurysms of the vertebral artery in terms of prevention of rebleeding. However, there is a risk of postprocedural medullary infarction in cases of perforating arteries originating from the dissected segment.